Academic motivations of pregrade students in the choice of international business career - Gonzales Silva, Brenda (2020)
The main objective of this research is to determine which is the most recurrent motivation by university students choose international business careers at 8 universities in Peru. The study sample is composed by 1242 international business students from the main universities in Peru. For this study, the Academic Motivation Scale (AMC) was used, this scale considers intrinsic motivation factors (knowledge, achievement, stimulating experiences), extrinsic motivation (identified regulation, introjected regulation, external introjected) and amotivation. As a result, the research shows that the students wanted to achieve their goals (84%), because it is aligned to their dreams (83%), also that they want to show to other people that they are capable to generate business opportunities (81%). On the other hand, the main demotivations were the fact that they don’t care and just want to finish the career (10%), they didn’t know which career choose (13%) and they didn’t know the reason why they choose this career (15%). It is concludes that the factors of academic motivations (motivation, extrinsic motivations and intrinsic motivations) are positively related to the choice of the international business career. Where the most significant relationship is that between extrinsic motivation with external regulation and the choice of the international commercial career, to achieve its objectives such as giving a more positive image to family and friends. While the least significant relationship is that between the intrinsic motivation for stimulating experiences and the choice of an international business career.